Line Identification of the Si Star HD 87240 - Saffe, Carlos (2004)
Line identifications are presented for the peculiar Apstar HD7240 (delta = - 59° 51´ 00.1´´) in the spectral region lambdalambda 3710-5520. This object is a member of the southern open cluster NGC114. Comparison of this object with other field silicon stars shows that it shares many of their line anomalies.